Comparison and evaluation of air cooling and water cooling in resource consumption and economic performance. (1st July 2018) - Zhang, Haitian; Feng, Xiao; Wang, Yufei
Abstract: Cooling systems have been widely applied in the process industry, which generally falls into two categories: air cooling and water cooling. Despite that both of these cooling types has their own specific advantages, resource consumption, especially energy and water, is inevitable to maintain system operation. Facing with overwhelming challenges in the industry field such as energy and water conservation, given selection of cooling type, it is imperative to take resource consumption and economy effect into account. In this paper, comparison among four different cooling types is carried out, including dry air coolers, spray type air coolers, evaporative air coolers, and circulating cooling water systems, for energy and water consumption and economy performance. Considering the cooling range from 95 °C to 40 °C, under circumstance of different dry bulb temperature and relative humidity, energy and water consumption can be calculated, while annual total cost, as a measure index of economic indication, is compared in the condition of different price ratio of fresh water and industrial electricity likewise. This work contributes to the determination of optimal cooling method, which has instructive significance in actual industrial processes. Highlights: Comparison among four different cooling types is carried out. Energy and water consumptions are compared. Ambient air temperature, relative humidity and price ratios as parameters. Total annual cost in different ambient air temperature and price ratio. Suitable cooling methods under different conditions.